The information-control systems efficiency assessment (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
The methodology for the information-control systems efficiency assessment is considered in this article. It is based on the information - probabilistic approach and the macroanalysis principles. The basic relation between the problem execution probability and the ICS information ability is determined. The dependence between number of elements ICS, information ability and cost efficiency index is considered. The ICS effectiveness and cost efficiency index is determined. The conditions under which it is possible to exchange some ICS parameters to others are defined. The effectiveness of ICS with conformed subsystems and with principal and providing subsystems is analyzed. The results enable to formalize the main system-information analysis problems, related to the efficiency assessment. Thus it is possible to consider the frequency - quantum characteristics or the frequency - quantum abilities and to assess the effectiveness and relative efficiency index, considering such system characteristics. The analysis is performed such a way it is possible to assess how the real system closer to the ideal.